A de novo ANK1 mutation associated to hereditary spherocytosis: a case report - Ti-Long Huang; Bao-Hua Sang; Qing-Ling Lei; Chun-Yan Song; Yun-Bi Lin; Yu Lv; Chun-Hui Yang; Na Li; Yue-Huang Yang; Xian-Wen Zhang; Xin Tian (BMC, 2019)
Abstract Background Hereditary spherocytosis (HS) is a type of hemolytic anemia caused by abnormal red cell membrane skeletal proteins with few unique clinical manifestations in the neonate and infant. An ANK1 gene mutation is the most common cause of HS. Case presentation The patient was a 11-month-old boy who suffered from anemia and needed a regular transfusion therapy at an interval of 2-3 months. Hematological investigations showed moderate anemia (Hb80 g/L). Red cells displayed microcytosis (MCV76.4 fl, MCH25.6 pg, MCHC335 g/L). The reticulocytes were elevated (4.8%) and the spherocytes were increased (10%). Direct antiglobulin test was negative. Biochemical test indicated a slight elevation of bilirubin, mainly indirect reacting (TBIL32.5 μmol/L, IBIL24 μmol/L). The neonatal HS ratio is 4.38, obviously up the threshold. Meanwhile, a de novo ANK1 mutation (exon 25:c.2693dupC:p.A899Sfs*11) was identified by next-generation sequencing (NGS). Thus, hereditary spherocytosis was finally diagnosed. Conclusions Gene detection should be considered in some hemolytic anemia which is difficult to diagnose by routine means. We identified a novel de novo ANK1 heterozygous frameshift mutation in a Yi nationality patient while neither of his parents carried this mutation.